A Systematic Review of Delayed Umbilical Cord Clamping to Reduce Anemia among Newborn Infants - Restuning Widiasih; Yulia Kurniawati; Ermiati Ermiati; Dinda Apriliani; Yasmina Suryadi; Ardyanti Syafitri; Tosin Popoola (Talenta Publisher, 2026)
Prolonged umbilical cord clamping during labour is one method to prevent anaemia in neonates; however, limited research on this treatment exists. This review aims to comprehensively assess the effects of delayed umbilical cord cutting and clamping on the anemia status of neonates. The review methodology employs a systematic review of the PubMed, CINAHL, and ScienceDirect databases. Keywords, inclusion and exclusion criteria are explicitly defined; the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) is used to examine article selection, and critical assessment is conducted using JBI for randomised controlled trials (RCTs). A total of 11 papers from various countries were selected. The analytical results indicate that umbilical cord clamping and cutting enhance placental transfusion, augment iron reserves, diminish the risk of baby anaemia, increase red blood cell flow, and improve cardiopulmonary adaption. This measure diminishes and averts the occurrence of anemia in babies. Restricted implementation and evaluation of the efficacy of this measure in developing and multicultural nations, such as Indonesia. The socialisation and integration of this action within health services enhances the health of newborns. Keyword: Anemia, Delayed cord clamping, Newborn